Reversing degradation of social-ecological systems: Explaining the outcomes of interventions in Africa - (:unkn) unknown (My University, 2025)
Social-ecological systems need to become more sustainable, especially in places undergoing rapid land degradation. The challenge is to reverse the depletion of natural resources while improving human well-being. This is especially critical in Africa where rural populations are often highly dependent on natural resources. Since the 1980s, several territories in Africa have initiated changes to reverse land degradation. This study aims at drawing lessons from these experiences. We identified seventeen cases of African territories that have engaged in sustainability interventions, either restoration or rehabilitation initiatives, with varying degrees of success. The key factors—grouped as information of key actors, their motivation to change practices, and their capacity to do so—that are recognized as potential success factors or obstacles for interventions towards sustainable resource use were analysed. Results highlighted the importance of maintaining a balance of factors over the long term. Managing sustainability transitions in low-income contexts requires integrating poverty-related concerns, mitigating the risks inherent to any change in practices, creating incentives for participation by all actors, and strengthening coalitions over the long term between actors around a sustainability agenda.
Keywords: African Research